Geology and distribution of heavy metals in topsoil, Kuala Krai, Kelantan. Issue 1 (August 2021) - Krishnan, R; Shafiee, N S; Bahar, A M A; Sulaiman, N
Abstract: The study for geology of Guchil, Kuala Krai, Kelantan was carried out approximately 25 km 2 in and around Guchil. Preliminary research and field studies conducted to produce geological map of Guchil, Kuala krai, Kelantan. Based on the field study carried, carbonaceous mudstone interbedded with greywacke sandstone, shale and ignimbrite distribution of rock found in this study. Meanwhile, investigation on distribution and potential heavy metals (Cu, Fe, Mn, Pb and Zn) in topsoil Guchil, Kuala Krai, Kelantan was conducted. Total of nine soil sample in and around Guchil undergo soil digestion and analyzed by Inductively Coupled Plasma Spectroscopy (ICP-OES). The heavy metals concentration in the topsoil was varied between 21176-138962; 649-8411; 11-505; 43-455; and 11-115 mg/kg for Fe, Pb, Mn, Zn and Cu respectively. The average concentration of heavy metals in this study followed the order of Fe > Pb > Mn > Zn > Cu. The spatial distribution pattern shows similar distribution pattern of heavy metals in residential area. The concentration of Cu, Fe, Mn, Pb and Zn from the soil samples compared with naturally occurring value of contaminated land management and control guidelines of Department of Environment Malaysia (DOE), 2009 and Barceloux (1999) as well as with permissible limit values in soil of Polish Ministry of the Environment, 2002. From this assessment method, highly potential element was Pb followed by Zn and Cu. Besides that soil characteristic of this study shows that soil pH which is acidic condition with low total organic matter. The soil fractions tend to dominated by clay fraction in topsoil.